EFFICACY AND SAFETY OF SUBCUTANEOUS LATERAL INTERNAL SPHINCTEROTOMY FOR CHRONIC ANAL FISSURE - Zubair, Muhammad; Saaiq, Muhammad; Shah, Syed Aslam (Journal of Ayub Medical College Abbottabad, 2014)
Background: This study was undertaken to determine the efficacy and safety of subcutaneous lateral internal sphincterotomy (SLIS) for chronic anal fissure by assessing the relief of defecatory pain, duration of wound healing and associated complications such as bleeding, infection, and anal incontinence. Methods: This descriptive case series was carried out at the Department of Surgery, Pakistan Institute of Medical Sciences (PIMS), Islamabad from September 1, 2008 to February 28, 2009. Results: Out of fifty patients 31 were males and 19 were females. The mean age was 30.04±8.49 years. Defecatory pain and bleeding per rectum were the commonest symptoms, found among all patients. Symptomatic relief of pain following surgery was observed among all patients at 4th week while all fissures healed at 8th week. At 4th weeks follow-up visit none of the patients had flatus incontinence while at 8th weeks all patients had good faecal continence. Majority (76%) of the patients were managed as Day case or Extended day case surgeries. There was no in-hospital mortality in this case series. Conclusion: SLIS is a valuable surgical procedure for patients with chronic anal fissure. It is effective and safe, offers quick relief of defecatory pain, and promotes early fissure healing without being attended by any major complications. The initial transient incontinence of flatus and faeces improves spontaneously over few weeks period. Majority of the patients are manageable on day case or extended day case surgery basis. Keywords: Chronic anal fissure. Subcutaneous lateral internal sphincterotomy, Day case surgery